HOW AUTO2000'S WORK CULTURE AND RULES SHAPE WORKERS' PRODUCTIVITY? - Ahmad Nizar Yogatama (Jurnal Ilmiah Global Education, 2022)
The purpose of this research is to investigate the extent to which the company's core values “Customer Focus”, “Integrity”, “Respect for Others”, “Strive for Excellence”, and “Teamwork” are reflected in the daily actions and decisions of workers branches through discipline and work environment. This study uses a quantitative approach. Saturation sampling, in which the entire population is used as the sample, is used for this purpose. Multiple linear regression analysis was performed to test responses to a questionnaire based on a Likert scale with five levels. This study found that the basic values of PT Toyota AUTO 2000 have a major influence in the form of discipline and work environment